The Effect of Using BLAST (Basic Local Alignment Search Tool) on the Conceptual Understanding of Students on Evolutionary Concepts - Allisa, Siti Nur; Sari, Indah Juwita; Rifqiawati, Ika; Ratnasari, Dwi (Cybersecurity and Innovative Technology Journal, 2026)
This study aimed to determine the effect of using the Basic Local Alignment Search Tool (BLAST) on students' learning independence and conceptual understanding of evolution at the senior high school level. The research uses a quantitative approach with a weak experimental, one-group pretest-posttest design. The study population consists of Grade XII Science students at a public senior high school in Tangerang, Indonesia. A random sample of 70 students formed the experimental group. Data collection used non-test methods, such as questionnaires for learning autonomy and essay tests for conceptual understanding. The average learning independence score was 79.1, indicating high independence. The average concept understanding score was 57.9, categorized as sufficient. Data analysis for learning independence used the Paired-Samples Test, while concept understanding was analyzed with the nonparametric Wilcoxon test. Results showed the use of BLAST had a significant effect on improving students' learning independence and conceptual understanding, with a p-value of 0.001 0.05.